Analysis and synthesis of evidence on the effects of investment in six Cycling Demonstration Towns. - Sloman, L.; Cavill, N.; Mueller, L.; Kennedy, A. (My University, 2009)
Der Bericht fasst die Veränderungen in Bezug auf Fahrradbenutzung und physischer Aktivität in sechs englischen Städten zusammen, die im Zuge eines Verkehrsinvestitionsprogrammes zwischen Oktober 2005 und März 2009 finanziell gefördert wurden. Dabei erhielten die ausgewählten Städte jährlich £500,000, die zusätzlich durch lokale Investitionen ergänzt wurden, so dass durchschnittlich £10 pro Einwohner und Jahr zur Förderung des Fahrradverkehrs investiert werden konnten.

This paper provides a summary of evidence on changes in cycling and physical activity in six towns following the first phase of the Cycling England / Department for Transport Cycling Demonstration Town investment programme between October 2005 and March 2009. The towns received funding of £500,000 per year (approximately £5 per head of population per year), starting in October 2005, and matched by the respective local authorities so that the total level of investment in cycling was at least £10 per head per year.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsinvestition; Mobilitätsverhalten; Fahrradbenutzung; Fahrradförderung; empirische Studie; Verkehrsunfall; Mobilitätsförderung; Verkehrsförderungsprogramm